2011 IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2011
DOI: 10.1109/isbi.2011.5872647
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and analysis of actin networks based on Open Active Contour models

Abstract: Network structures formed by actin filaments are present in many kinds of fluorescence microscopy images. In order to quantify the conformations and dynamics of such actin filaments, we propose a fully automated method to extract actin networks from images and analyze network topology. The method handles well intersecting filaments and, to some extent, overlapping filaments. First we automatically initialize a large number of Stretching Open Active Contours (SOACs) from ridge points detected by searching for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Unlike previous methods that relied on a global intensity contrast (Li et al, 2009a; Smith et al, 2010; Xu et al, 2011), Equation 7 generates stretching force that is adaptable according to local intensity contrast around SOAC tips. This can avoid under-segmentation for dim filaments in low-intensity backgrounds or over-segmentation for bright filaments in high-intensity backgrounds.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike previous methods that relied on a global intensity contrast (Li et al, 2009a; Smith et al, 2010; Xu et al, 2011), Equation 7 generates stretching force that is adaptable according to local intensity contrast around SOAC tips. This can avoid under-segmentation for dim filaments in low-intensity backgrounds or over-segmentation for bright filaments in high-intensity backgrounds.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study (Xu et al, 2011), we have shown how multiple Stretching Open Active Contours (SOACs) that elongate and merge with one another can be used to segment networks of actin filaments in 2D TIRFM images, such as in Figure 1(a). In this article we present an extension and significant modification of the multiple SOACs method to address the more complex issues that arise in 3D and to propose mechanisms that make the approach robust to heavy image noise, non-uniform filament and background intensity, and anisotropic sampling as are typical in many 3D experimental images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported automated two-dimensional methods that distill stacks of images into filament locations and network topologies [29] (Fig. 3D) could be extended to three dimensions.…”
Section: Analyzing the Morphology Of Actin Cablesmentioning
confidence: 99%
“…A fit to a double exponential (continuous line) leads to length scales l 1 = 2 μ m and l 2 = 1 mm [28]. (D) Automatic segmentation of 2D filament network using multiple active contours from [29]. A meshwork is generated by initialization of multiple active contours at ridge points followed by growth, merging and splitting of active contours.…”
Section: Figmentioning
confidence: 99%